ANALISIS KEBIJAKAN IMPOR BERAS DI INDONESIA DALAM KERANGKA SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Sudarto, Sudarto; Muhtadin, Muhtadin (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2024)
This study aims to analyze the substance and implementation of Indonesia’s rice import policy within the framework of the Sustainable Development Goals (SDGs), focusing on Central Java Province as one of the country’s major rice-producing regions. The research employed a qualitative approach using policy analysis. Data were collected through the examination of national policy documents, statistical reports, and in-depth interviews with regional stakeholders. The analysis applied content analysis and thematic analysis based on SDG indicators, particularly SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production). The findings indicate that rice import policies play a significant role in maintaining national food supply stability and controlling price fluctuations, particularly during periods of domestic production decline. However, their implementation in Central Java presents challenges, especially regarding the synchronization of import timing with harvest seasons and the protection of farmers’ welfare. Overall, while the policy aligns with food supply stability objectives, stronger integration of long-term sustainability principles is required to support a resilient and inclusive food system.